Les conditions de l’excellence administrative dans les organisations des affaires: Etude descriptive et analytique - SAAL, Soumia (Finance and Business Economies Review, 2023)
Many organisations seek administrative excellence, but few are able to achieve this goal because the majority are not fully aware of the meaning of excellence because it is a systematic framework for development through a set of standards, these standards evolved with the development of management sciences. The interest in excellence is not recent, because there are many studies that have dealt with the concept of administrative excellence in the past, present and future that can be obtained by preference in performance, whether in product or service